DAK FISIK KESEHATAN TO REDUCE MATERNAL AND INFANT MORTALITY RATE - Alvaro, Rendy; Christianingrum, Ratna; Riyono, Tio (UI Scholars Hub, 2022)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are essential indicators of health development that are written on the national development plan documents. Nevertheless, Indonesia has not yet achieved the national target of MDG’s and SDG’s. In prediction, without extraordinary policies, the target of SDGs will not be reached by 2030. The government has allocated DAK Fisik Penugasan as one of the efforts to reduce MMR and IMR. So this study aims to capture the effect of DAK Fisik in decreasing MMR and IMR. Panel data from 34 provinces level in 2019 and 2020 are analyzed using mean difference test and quadrant analysis. Results show that there is no significant difference of MMR in 34 provinces with or without DAK Fisik Penugasan. Then there are still many provinces with the lower MMR and IMR which get budget priorities and vice versa. The government should 1) provide a local government stimulus to enhance acceleration of reducing MMR and IMR; 2) allocate budget priority to provinces that have higher score of MMR and IMR; 3) Encourage local governments to improve the quality of DAK Fisik proposals along with better quality of budget absorption.